Effects of resisted-sprint training on sprint performance and mechanics: A systematic review and meta-analysis focusing on load magnitude - Xu, K.; Jukic, I.; Cross, M. R.; Hicks, D. S.; Yin, M. Y.; Zhong, Y. M.; Tang, W. J.; Li, Y. F.; Liang, Z. D.; Wang, R.; Morin, J.-B.; Girard, O. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Resisted sprint training (RST) is effective for improving sprint acceleration. However, the choice of RST loads-ranging from light (<= 10% of unresisted sprint maximum velocity decrement [vdec], < 20% of body mass [BM]) to very heavy (>= 50% vdec or >= 80% BM) -remains debated. To (i) explore the effects of different RST loads and unresisted sprint training (UST) on sprint performance and macroscopic mechanical outputs (e.g., theoretical maximal horizontal force [F0], power [Pmax], maximal ratio of horizontal-to-resultant force [RFmax]), and (ii) investigate how participant characteristics and training parameters influence sprint performance at varying RST loads. A search of 10 databases was conducted until September 2024, with studies included if they involved longitudinal interventions using horizontal resistance (e.g., sled) and if RST was the primary difference in training between groups. Analyses included single-arm (RST pre vs. post, considered exploratory only), two-arm (RST vs. UST), and multi-arm comparisons (different RST loads, UST, and control). Analytical models included two-level, three-level, and Bayesian-based network meta-analysis. The effects of different moderators on sprint performance and mechanical characteristics were explored through subgroup analyses and meta-regressions. Certainty of evidence was assessed using the GRADE approach. A total of 49 RST studies (1281 participants: 1153 males, 160 females, 64 unclear) were included. Pooled results showed RST was more effective than UST for improving sprint performance (effect size [ES] = -0.30, Hedges' g, Moderate GRADE). However, only moderate (>= 20%-50% BM or > 10%-30% vdec) and very heavy RST were more effective than UST, whereas light and heavy loads (> 50%-80% BM or > 30%-50% vdec) were not. Two- and multiple-comparison models indicated that very heavy RST loads produced significantly greater performance improvements than light loads. The effect of RST on performance compared to UST became more pronounced with an increasing load (ß = -0.005, p = 0.018), with a significant threshold at 20.7% BM, beyond which RST led to significantly greater performance improvements than UST (p < 0.05). Very heavy RST loads were particularly effective in improving F0, Pmax, and RFmax compared to UST, with adaptations in F0 increasing significantly in tandem with RST (ß = 0.010, p = 0.023). These effects were more pronounced in trained and highly trained individuals, with negligible improvements in recreationally active participants. There was an inverted U-shaped relationship between training volume (total distance) and training effect: heavy loads at small volumes yielded similar benefits to light loads at large volumes. Finally, participant characteristics (age, sex) and training parameters (duration, frequency, number of training sessions, sprint phase, session volume) also influenced sprint performance improvements. Very heavy loads were generally more effective at increasing sprint performance than UST and light RST loads, with light RST showing comparable effects to UST. These findings were likely attributable to improvements in the early acceleration phase (especially 0-5 m). Heavier loads were optimal for trained and highly trained groups, but no clear benefit of higher loads for recreational groups, suggesting light RST or UST are probably sufficient. Coaches and practitioners can refine protocols based on these findings to boost sprint performance outcomes.